Financial Analysis of 18kW Solar Photovoltaic Baidi Microgrid at Baidi, Tanahun, Nepal - Neupane, Sanjaya; Jha, Ajay Kumar; Sah, Anirudh Prasad (Journal of the Institute of Engineering, 2020)
This study presents financial evaluation of 18 kW solar photovoltaic powered Baidi Micro Grid implemented by Alternative Energy Promotion Center (AEPC) in Dubung village, Rising Gaupalika, Tanahun district of Nepal. The grid is built and is operational under Baidi Micro Grid Pvt. Ltd, a Special Purpose Vehicle (SPV) established under “Pro-Poor Public Private Partnership (5P)” concept supported by United Nations Economic and Social Commission for Asia and the Pacific (UNESCAP) & International Fund for Agricultural Development (IFAD). It is pilot project under 5P concept in Nepal. People from Dubung and Mauribas village as well as Saral Urja Nepal Pvt Ltd (SUN) jointly owns the SPV strengthening not only technical, managerial and financial support but also the community participation and engagement in all decision making process. The total cost of the project is NPR 13,395,000.00 at 2015 AD. The grant for the project was of value NPR 11,295,000.00 from AEPC, IFAD and UNESCAP and remaining was equity of SUN. The net present value of NPR -10,978,605.76 is obtained at 3% discount rate due to unavoidable replacement cost of batteries, charge controllers, inverters and high initial investment without the consideration of the grant amount. Whereas, with 84.32% utilization of available grant, the NPV worth of NPR 384,394.22 is obtained for the project. In breakeven analysis, a breakeven point of the project is obtained at 81.87% utilization of the grant. Without grant, project like Baidi Micro Grid will not sustain. In addition, average unit cost of electricity is found to be NPR 37.08 but it varied from NPR 16.67 to NPR 80.81. Household consuming more electricity has to pay less unit cost of electricity whereas household consuming less electricity had to pay higher unit cost of electricity.